Oxysterol-binding protein related-proteins (ORPs) 5 and 8 regulate calcium signaling at specific cell compartments. (June 2018) - Pulli, Ilari; Lassila, Taru; Pan, Guoping; Yan, Daoguang; Olkkonen, Vesa M.; Törnquist, Kid
Graphical abstract: Highlights: ORP5 and -8 localize at ER-mitochondria and ER-plasma membrane contact sites. ORP5 or -8 overexpression elevates calcium levels in the mitochondrial matrix and at caveolae. ORP5 or -8 overexpression augments cell proliferation. Our data suggest that ORP5/8 regulate calcium signaling at specific membrane contacts. Abstract: Oxysterol-binding protein related-protein 5 and 8 (ORP5/8) localize to the membrane contact sites (MCS) of the endoplasmic reticulum (ER) and the mitochondria, as well as to the ER-plasma membrane (PM) MCS. The MCS are emerging as important regulators of cell signaling events, including calcium (Ca 2+ ) signaling. ORP5/8 have been shown to interact with phosphatidylinositol-4, 5-bisphosphate (PIP2 ) in the PM, and to modulate mitochondrial respiration and morphology. PIP2 is the direct precursor of inositol trisphosphate (IP3 ), a key second messenger responsible for Ca 2+ -release from the intracellular Ca 2+ stores. Further, mitochondrial respiration is linked to Ca 2+ transfer from the ER to the mitochondria. Hence, we asked whether ORP5/8 would affect Ca 2+ signaling in these cell compartments, and employed genetically engineered aequorin Ca 2+ probes to investigate the effect of ORP5/8 in the regulation of mitochondrial and caveolar Ca 2+ . Our results show that ORP5/8 overexpression leads to increased mitochondrial matrix Ca 2+ as well as to increased Ca 2+ concentration at the caveolar subdomains of the PM during histamine stimulation, while having no effect on the cytoplasmic Ca 2+ . Also, we found that ORP5/8 overexpression increases cell proliferation. Our results show that ORP5/8 regulate Ca 2+ signaling at specific MCS foci. These local ORP5/8-mediated Ca 2+ signaling events are likely to play roles in processes such as mitochondrial respiration and cell proliferation.